2006
DOI: 10.1242/dev.02326
|View full text |Cite
|
Sign up to set email alerts
|

Sp8controls the anteroposterior patterning at the midbrain-hindbrain border

Abstract: The specification of neuronal cell types in the developing neural tube is orchestrated by signaling centers. However, how patterned territories of the central nervous system (CNS) are organized into structures with appropriate size and shape is still unclear. We report that in the absence of the mouse transcription factor mBtd/Sp8, a posterior shift of the isthmic organizer (IsO) occurs, suggesting a crucial role for Sp8 in this process. In addition, large patches of cells ectopically expressing Fgf8, Otx2 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 41 publications
2
11
0
Order By: Relevance
“…4 G and H). A posterior shift of gbx2 expression was observed, consistent with the previous study of sp8 as a midbrain-hindbrain boundary regulator (16). Although the ecl mutation did not show the severe head defects reported for the mouse, these expression analyses reveal that sp8 still has a conserved function to regulate brain development.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…4 G and H). A posterior shift of gbx2 expression was observed, consistent with the previous study of sp8 as a midbrain-hindbrain boundary regulator (16). Although the ecl mutation did not show the severe head defects reported for the mouse, these expression analyses reveal that sp8 still has a conserved function to regulate brain development.…”
Section: Resultssupporting
confidence: 89%
“…The zinc-finger transcription factor sp8 is related to Drosophila buttonhead. In mice, mutation of sp8 caused severe truncations of the limbs and tail and defective brain and abnormal olfactory development (14)(15)(16)(17). Limb/fin outgrowth in chick and zebrafish embryos also employs sp8 (18), suggesting the conserved function of sp8 across phylogeny.…”
mentioning
confidence: 99%
“…Sp8 is part of a transcriptional program that patterns neural progenitors into distinct domains (Griesel et al 2006;O'Leary et al 2007;Sahara et al 2007;Zembrzycki et al 2007;Kasberg et al 2013); however, a transcriptional network involving Sp8 during neural tube closure has not yet been identified. It will be interesting to determine whether there are shared targets of sptf-3 and Sp8.…”
Section: Discussionmentioning
confidence: 99%
“…6A). The physiological role of Sp8 in ameloblasts remains to be determined, although it has been reported that Sp8 is expressed during brain and limb bud development and demonstrated to regulate cortical patterning and limb outgrowth through FGF8 induction (26,27). In addition, gene expression of ameloblastin, one of the enamel-producing proteins, was significantly up-regulated in CHA9 cells compared with V1 cells (Fig.…”
Section: Discussionmentioning
confidence: 99%